Sanções processuais por ato atentatório ao exercício da jurisdição : instrumento de efetividade das decisões judiciais - Severino, Renata Cortez Vieira (2007)
This study aimed at the system of the subject concerning applicable procedural sanctions as the result of contempt of court practice related to the non-compliance with judicial decisions and presentation of solutions to existing contradictions in the brazilian legislation and jurisprudence on the theme in order to help improve the procedural theory; to encourage the use by courthouses of procedural sanctions that stem from contempt of court; and to provide a base for legislation change of the articles which deal with the subject. The research was based on the use of primary and secondary sources as follows: research on bibliography, national and foreign literature as well as the use of a file: books, journals and internet articles; study of law that is applicable to the subject: jurisprudential research at the Supremo Tribunal Federal, at the Tribunais Regionais Federais and brazilian Court Houses, as well as in foreign courts: Supremo Tribunal de Justiça of Portugal; Court of Appeals of North Carolina (USA); Supreme Court of Canada; and High Court and Court of Appeal (Civil Divisions) in England and Wales. After the analysis of the pertaining doctrine, legislation and jurisprudence, we came to the conclusion that the contempt of court in Brazil is contradictory and insufficient, being necessary the standard of improvement of rules of the Code of Civil Procedure about the subject, since the effectiveness of the institute studied is of the utmost importance to the effectiveness of judicial decisions that, by its turn, is a must when it comes to the dignity of justice and guarantee of effective jurisdiction.